Mandatory climate risk disclosure, housing prices, and credit supply - Chen, Xi (Review of Accounting Studies, 2026)
This paper examines how climate risk transparency influences house prices and credit supply. I contend that inadequate property-level climate risk disclosures induce homebuyers to demand a risk aversion discount on house prices, creating a potential market for lemons. Employing a stacked difference-in-differences design, I find that flood risk disclosure laws, by enhancing dwelling-specific flood risk transparency, raise house prices on average by 7.6%. Results strengthen in states with stricter disclosure requirements. Exploiting within-state heterogeneity and controlling for housing market trends, I find that the effects persist and intensify in regions with higher aggregate exposure to flood risk, greater information frictions, and more attention to climate risks. Conversely, the effectiveness of flood risk disclosure laws attenuates in regions where households are less concerned about climate change. Additionally, less sophisticated lenders extend credit to financially constrained borrowers in response to the laws but experience lower profitability.